An Outline of the Recent History of Indonesian Criminal Law - Bing Siong, H. (Brill, 1961)
Indonesia
English
Keywords: Asian history; indonesia; Adat; Criminal code; Criminal law; Dutch East Indies; Jakarta; Java; Kalimantan; State of East Sumatra; Sumatra